-6g+3G=2+4

Simple and best practice solution for -6g+3G=2+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6g+3G=2+4 equation:


Simplifying
-6g + 3G = 2 + 4

Reorder the terms:
3G + -6g = 2 + 4

Combine like terms: 2 + 4 = 6
3G + -6g = 6

Solving
3G + -6g = 6

Solving for variable 'G'.

Move all terms containing G to the left, all other terms to the right.

Add '6g' to each side of the equation.
3G + -6g + 6g = 6 + 6g

Combine like terms: -6g + 6g = 0
3G + 0 = 6 + 6g
3G = 6 + 6g

Divide each side by '3'.
G = 2 + 2g

Simplifying
G = 2 + 2g

See similar equations:

| -4(4t^2-12t-216)=0 | | a(n+2)+n+2= | | 3x-9+9=15+12 | | 3(x-1)=-2x+5 | | x+.20x=925.20 | | 2x(n-1)+3y(n-1)= | | 30x+60=400 | | 8(x+10)-7X=120 | | 30(x-30)=400 | | m(a-b)+(a-b)= | | -56a-6=10 | | 0.8=8 | | p(35)=-9p+4 | | 56-6=10 | | (-4x^3p^2)(4y^3x^3)=0 | | 2(x-1)+y(x-1)= | | 57a-8=11 | | 1/4x-12=1/4 | | 57a-7=14 | | x+.06x=151.88 | | 20-8=28+2 | | x(a+1)-3(a+1)= | | -3/8x7 | | x+.5x=191.10 | | 2(u-1)-2=-6(-3u+2)-6u | | 3x-(2x-1)=9 | | p(28)=5p-17 | | x-.65x=224 | | X-5-2(X-1)=2(3-3) | | 90=x+4+3x+2 | | 6/(-3)(4) | | 1x-12=-12 |

Equations solver categories